Tethered Membrane Architectures—Design and Applications - Andersson, Jakob; Köper, Ingo; Knoll, Wolfgang (Frontiers in Materials, 2018)
Membrane proteins perform a large number of essential biological tasks, but the understanding of these proteins has progressed much more slowly than that of globular proteins. The study of membrane proteins is hindered by the inherent complexity of the cellular membrane. Membrane proteins cannot be studied outside their native environment because their natural structure and function is compromised when the protein does not reside in the cell membrane. Model membranes have been developed to provide a controlled, membrane-like environment in which these proteins can be studied in their native form and function without interference from other membrane components. Traditionally used model membranes such as bimolecular or black lipid membranes and floating lipid membranes suffer from several disadvantages including complex assembly protocols and limited stability. Furthermore, these membranes can only be studied with a narrow range of methodologies, severely restricting their use. To increase membrane stability, simplify the assembly process and increase the number of analytical tools that can be used to study the membranes, several strategies of covalently tethering the bilayer to its solid support have been developed. This review provides an overview of the methods used to assemble various membrane architectures, the properties of the resulting membranes and the tools used to study them.